1997
DOI: 10.2136/sssaj1997.03615995006100030038x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Chamber Measurements of Methane and Nitrous Oxide Flux in a Flooded Rice Soil: I. Residue, Nitrogen, and Water Management

Abstract: Methane and N2O are gases that are several times more radiatively active than CO2. It is well known that flooded rice (Oryza sativa L.) soils are a globally important source of atmospheric CH4. Mitigation strategies for CH4 flux, such as mid‐season drainage, might have the opposite effect on N2O emissions. An automated chamber system at the International Rice Research Institute in the Philippines measured CH4 and N2O fluxes from flooded rice and fallow rice fields essentially 24 h a day between December 1992 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
90
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(115 citation statements)
references
References 0 publications
17
90
1
5
Order By: Relevance
“…These results were similar to the measured diurnal variations reported previously [2] [4] [6]- [13]. Though greater diurnal variations have been reported early compared to late in the growing season [8] [10], results of this study indicated the proportional range in diurnal CH 4 fluxes/estimated emissions was similar before and after heading from both soil textures (Table 3). The numeric peak CH 4 flux was 23% to 33% greater than the numeric low among the various measurement times of day across the four location-growth stage combinations, which was similar to the magnitude of variation reported by Yagi and Minami [13].…”
Section: Hourly Ch4 Fluxes and Estimated Daily Emissionssupporting
confidence: 91%
See 3 more Smart Citations
“…These results were similar to the measured diurnal variations reported previously [2] [4] [6]- [13]. Though greater diurnal variations have been reported early compared to late in the growing season [8] [10], results of this study indicated the proportional range in diurnal CH 4 fluxes/estimated emissions was similar before and after heading from both soil textures (Table 3). The numeric peak CH 4 flux was 23% to 33% greater than the numeric low among the various measurement times of day across the four location-growth stage combinations, which was similar to the magnitude of variation reported by Yagi and Minami [13].…”
Section: Hourly Ch4 Fluxes and Estimated Daily Emissionssupporting
confidence: 91%
“…However, numerous studies have also reported no significant difference in CH 4 emissions between day and night [6] [14] [15]. Differences between cultivars have generally been consistent given the multitude of factors that have been shown to affect CH 4 fluxes and emissions throughout a growing season, such as soil texture [16] [17] [18] [19], fertilizer nutrient source [20], organic soil amendments [8] [12], residue management/previous crop [21] [22] [23] [24], water management scheme [8] [25] [26], and production system [27]. Typically, hybrid rice cultivars have lower season-long CH 4 emissions than do pure-line cultivars [23] [24] [28] [29].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Methane emissions are stimulated by organic amendments (Watanabe et al, 1995;Bronson et al, 1997), but this effect may be due partly to lower CH 4 oxidation caused by more rapid heterotrophic 0 2 consumption at the soil surface.…”
Section: Carbon Quantity and Qualitymentioning
confidence: 99%